2022
DOI: 10.1155/2022/3261213
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] DNMT3A Regulates miR‐149 DNA Methylation to Activate NOTCH1/Hedgehog Pathway to Promote the Development of Junctional Osteosarcoma

Abstract: Purpose. To investigate the DNMT3A/miR-149/NOTCH1/Hedgehog axis regulating the development of osteosarcoma. Methods. First, microRNA and mRNA expression microarrays were downloaded from the GEO database for osteosarcoma and differentially expressed microRNAs were analyzed. Subsequently, we collected cancerous tissues and corresponding paracancerous tissues from 42 osteosarcoma patients and examined the expression levels of miR-149, DNMT3A, and NOTCH1 in the samples. Subsequently, miR-149 was overexpressed in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Among these, DNA methyltransferases (DNMTs), particularly DNMT3A, have been pinpointed as critical in suppressing miR-149 expression via DNA methylation. This suppression subsequently activates the NOTCH1 and Hedgehog pathways, fueling osteosarcoma growth and metastasis [ 30 ]. The emerging role of long non-coding RNAs (lncRNAs) in this context is evident in molecules like THAP9-AS1.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, DNA methyltransferases (DNMTs), particularly DNMT3A, have been pinpointed as critical in suppressing miR-149 expression via DNA methylation. This suppression subsequently activates the NOTCH1 and Hedgehog pathways, fueling osteosarcoma growth and metastasis [ 30 ]. The emerging role of long non-coding RNAs (lncRNAs) in this context is evident in molecules like THAP9-AS1.…”
Section: Resultsmentioning
confidence: 99%
“…The enhanced catalytic activity of DNMT3A is associated with cancer development and progression. Cheng et al reported that DNMT3A facilitated OS progression by mediating miR-149 DNA methylation to activate the Notch1/Hedgehog pathway [ 43 ]. In line with the former study, DNMT3A’s carcinogenic role in OS was also recognized herein, and miR-186 suppressed OS by decreasing DNMT3A.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis of OS cells showed hypermethylation of CGI CpG79 upstream of miR-486-5p [ 17 ]. In a study by Cheng and Wang et al, 2022, DNA methylation was similarly found to be responsible for the suppression of miRNA [ 18 ]. miR-149 was underexpressed in OS samples, and less expression correlated with higher-stage tumors.…”
Section: Methylationmentioning
confidence: 99%